Why Street Vendors appeared Unplanned in a Planned City? A Case Study with Special Reference to Bidhannagar Planned Township in Kolkata, West Bengal - Bhattacharjee, Chandrani; Das, Narasingha; Pal, Prof. Mihir Kumar (IJRDO - Journal of Social Science and Humanities Research, 2018)
Street vendors, as a part of India’s informal sector employment, provide various types of services; though they are persecuted by the municipal authorities and the police. Bribery is the only way most street vendors can survive in their trade. The working conditions of the hawkers are very poor and most hawkers lead a very hard life. In this paper, we are tries to analyse the facts behind engaging in the street vending job by the vendors, coming from various part of our country, in the Bidhannagar planned city of Kolkata in West Bengal. In this regard, through a primary survey followed by a scheduled questionnaire we conduct the study. This study also postulates some policy measures which are essential in improving the economic as well as social benefits for the vendors as well as for the society. From our study, we found that the main cause behind the problem of Street Vendors in a planned city like Bidhannagar Town is that the Planners did not think that the staff of different offices (Government as well as Private) would need food during break i.e. necessary condition was not considered. Alternatively to fulfil the necessary condition the offices located here might arrange for internal canteen yet general human psychology is that she / he always finds many options and choices. Therefore, dependency on street vendors is inevitable, because a strong demand is exist that can only be satisfied with the items supplied by the street vendors. There is no other alternative. So the street vendors must be given their due attention. Otherwise the conveniences of planned city cannot be enjoyable in the long run. It will transform to a non-planned city – no control, no sustaining of development. Bidhannagar town is already struggling to provide a basic quality of life and livelihood security of the poor vendor is far behind.